Logos of Phenomenology and Phenomenology of the Logos. Book One Phenomenology as the Critique of Reason in Contemporary Criticism and Interpretation - Tymieniecka, Anna-Teresa (Analecta Husserliana, The Yearbook of Phenomenological Research, 2005)
During its century-long unfolding, spreading in numerous directions, Husserlian phenomenology while loosening inner articulations, has nevertheless maintained a somewhat consistent profile. As we see in this collection, the numerous conceptions and theories advanced in the various phases of reinterpretations have remained identifiable with phenomenology. What conveys this consistency in virtue of which innumerable types of inquiry-scientific, social, artistic, literary - may consider themselves phenomenological? Is it not the quintessence of the phenomenological quest, namely our seeking to reach the very foundations of reality at all its constitutive levels by pursuing its logos? Inquiring into the logos of the phenomenological quest we discover, indeed, all the main constitutive spheres of reality and of the human subject involved in it, and concurrently, the logos itself comes to light in the radiation of its force (Tymieniecka).